Economic growth and quality of institutions in 27 postsocialist economies - Alexiou, Constantinos; Vogiazas, Sofoklis; Solovev, Nikita (Emerald, 2020)
Purpose – The relationship between institutional quality and economic growth is revisited. Design/methodology/approach – A panel cointegration methodology and causality analysis are applied to 27 postsocialist economies over the period from 1996 to 2016. Findings – Utilizing the Worldwide Governance Indicators as a means of assessing the quality of institutions, it is found that in the long run, economic growth is positively associated with the rule of law and voice and accountability. In the short run, regulatory quality retains a positive effect, but voice and accountability demonstrate a puzzling negative effect on economic growth that merits further analysis. In exploring the causal dimension of our variables, supporting evidence of the strong links between the quality of institutions and economic growth is provided, hence rendering robust results. Originality/value – To the best of the authors’ knowledge, it is the first time that an ARDL methodological framework, which addresses potential endogeneity issues, is used to investigate the relationship between institutional quality and growth in the context of postsocialist economies.
Keywords: Economic growth; Post-Socialist Economies; Institutions; Governance Indicators; Panel Cointegration; Causality